Kontribusi Kepemimpinan Situasional, Supervisi Akademik, Iklim Kerja dan Motivasi Kerja Terhadap Komitmen Organisasional Guru di SMA di Kecamatan Mendoyo - D.A.K.M.C. Dewi; A.A.G. Agung; I.M. Yudana (Pascasarjana Universitas Pendidikan Ganesha, 2022)
This study aims to determine the magnitude of the variable contribution of situational leadership, academic supervision, work climate, and work motivation to the organizational commitment of high school teachers in the Mendoyo District. This type of research is ex post facto with multiple linear regression analysis designs. The population in this study amounted to 86 people. The entire population is used as a research sample, so this is a population study. The data was collected using a closed-choice questionnaire using the Sala Likert model. The results of this study indicate that (1) there is a contribution of situational leadership to the organizational commitment of 15.46%, 2) there is a contribution of academic supervision to teacher organizational commitment of 38.34%, (3) there is a contribution of work climate to teacher organizational commitment of 5.89% (4) there is a contribution of work motivation to teacher organizational commitment of 13.08% (5) there is a simultaneous contribution to situational leadership, academic supervision, work climate, and work motivation to teacher organizational commitment of 72.77%.